KOMPOSISI JENIS, STRUKTUR TEGAKAN DAN DIVERSITAS VEGETASI HUTAN BAKAU DI PULAU KARAMIAN KABUPATEN SUMENEP JAWA TIMUR - Mohammad Jufri; Gusti Syeransyah Rudy; Kissinger Kissinger (Universitas Lambung Mangkurat, 2022)
Mangroves become forest ecosystems with extreme physical factors, waterlogged habitats with high salinity located on beaches and rivers. Soil conditions in muddy. Mangrove forests become one of the important economic sources for people who live in the marine area of Karamian Island. The purpose of this study is to analyze the composition of mangrove forest vegetation types on keramian island, analyze horizontal vegetation structures in mangrove communities and analyze the deversity of mangrove forest diversity types. This study uses observation method with purposive sampling data collection technique as much as 3 research plots with a length of 200 m each plot. Important value index (INP) of Rhizopora sp tree (142.11 %), rhizopora sp pole level (275.79 %) and seedling level Rhizopora sp ( 88.84 %) with the diversity of species or diversity of mangrove forests on karamian island is still relatively low at every level of vegetation that has been observedHutan bakau (Mangrove) menjadi ekosistem hutan dengan faktor fisik yang ekstrim, habitat tergenang air dengan salinitas tinggi yang berada di pantai dan sungai. Kondisi tanah pada hutan mangrove berlumpur. Hutan bakau menajadi salah satu sumber ekonomi penting bagi manusia yang berada dan tinggal di wilayah perisir laut Pulau Karamian. Tujuan penelitian ini untuk menganalisis komposisi jenis vegetasi hutan mangrove di pulau Keramian, menganalisis struktur vegetasi horizontal pada komunits mangrove serta menganalisis deversitas jenis keragaman hutan mangrove. Penelitian ini menggunakn metode observasi dengan dengan teknik pengambilan data purposive sampling sebanyak 3 plot penelitian dengan panjang masing-masing plot 200 m. Indeks nilai penting (INP) tingkaat pohon Rhizopora sp (142,11 %), tingkat tiang Rhizopora sp (275,79 %) dan tingkat semai Rhizopora sp ( 88,84 %) dengan diversitas jenis atau keragaman hutan mangrove di pulau Karamian masih tergolong rendah pada setiap tingkat vegetasi yang telah diamati